The influence of self-confidence on high school students learning outcomes in solving SLETV question - Isna Luthfi Atin Nisa’; Rizqona Maharani (Journal Focus Action of Research Mathematic (Factor M), 2025)
Education is a key foundation for holistic student development, encompassing both academic achievement and character building. Among internal factors, self-confidence plays a crucial role in achieving optimal learning outcomes and overcoming challenges, including solving problems on the System of Linear Equations in Three Variables (SLETV). This study aims to analyze the influence of self-confidence on students’ learning outcomes in solving SLETV problems. A quantitative correlational design was employed, involving 30 grade X students at SMA Hidayatul Mustafidin selected through random sampling. Data were collected using a self-confidence questionnaire and an essay test on SLETV, and analyzed through simple linear regression. The results show that self-confidence has a substantial and significant effect on learning outcomes (R² = 0.898), indicating that self-confidence contributes substantially, although other factors also influence achievement. The regression equation obtained is Y = -4.070 + 1.068X. These findings highlight the importance of fostering students’ self-confidence in mathematics learning, particularly in SLETV, as a means to enhance problem-solving performance and overall academic success.